Improving health, wellbeing and parenting skills in parents of children with special health care needs and medical complexity - a scoping review - Sally Bradshaw; Danai Bem; Karen Shaw; Beck Taylor; Christopher Chiswell; Mary Salama; Eve Bassett; Geetinder Kaur; Carole Cummins (BMC, 2019)
Abstract Background Parenting children with special health care needs can be challenging particularly if children have complex conditions. Parents may struggle to manage their child's health and their own emotions, contributing to poorer health outcomes for the family. Frequent healthcare contact presents opportunities to intervene, but current evidence review is limited. This review scopes and synthesizes interventions to improve health, wellbeing and parenting skills. Methods Using formal scoping review methodology MEDLINE, EMBASE, PsycINFO, CINAHL, The Cochrane Library, ERIC, ASSIA, HMIC and OpenGrey were searched to February 2017. Citations were double screened according to predetermined eligibility criteria. Data were extracted and synthesized on study design, population, measurement tools, and results. Results Sixty-five studies from 10,154 citations were included spanning parenting programs, other parent behavior change interventions, peer support, support for hospital admission and discharge and others. Interventions for parents of children with a wide range of conditions were included. These targeted a broad selection of parent outcomes, delivered by a wide variety of professionals and lay workers. Most studies reported positive outcomes. No serious adverse events were noted but issues identified included group and peer relationship dynamics, timing of interventions in relation to the child's disease trajectory, the possibility of expectations not fulfilled, and parent's support needs following intervention. Children with medical complexity were not identified explicitly in any studies. Conclusions The range of interventions identified in this review confirms that parents have significant and diverse support needs, and are likely to benefit from a number of interventions targeting specific issues and outcomes across their child's condition trajectory. There is much scope for these to be provided within existing multi-disciplinary teams during routine health care contacts. Careful tailoring is needed to ensure interventions are both feasible for delivery within routine care settings and relevant and accessible for parents of children across the complexity spectrum. Further review of the existing literature is needed to quantify the benefits for parents and assess the quality of the evidence. Further development of interventions to address issues that are relevant and meaningful to parents is needed to maximize intervention effectiveness in this context.